THE EFFECT OF ROUND ROBIN BRAINSTORMING STRATEGY IN SOLVING SPEAKING ANXIETY OF TENTH GRADE STUDENTS OF SMK MUHAMMADIYAH PAGARALAM - Sri Wahyuni; Kurnia Febianti; Laras Margaretha (Universitas PGRI Palembang, 2023)
The aimed of this research was to find out the effect of Round Robin Brainstorming in solving students’ speaking anxiety. the writer compared level of students’ speaking anxiety and students’ speaking ability to find out the effect of Round Robin Brainstorming before and after being taught by Round Robin Brainstorming. The researcher took one class as the sample that consist of 30 students from X Multimedia 2 of SMK Muhammadiyah Pagaralam. The data was collected by using two instruments. The first is a speaking test to measure students' speaking ability, The second instrument used was a questionnaire sheet (FLCAS) consisting of 33 items that adopted from Horwitz et al (1986) with scoring Likert’s scale and analyzed manually used Oetting’s scale to categorize students’ speaking anxiety levels. The result showed that there was significant progress in the students’ speaking ability and students’ speaking anxiety was reduce after being taught by using round robin brainstorming strategy.